‘No black and white answer about how far we can go’: police decision making under the domestic violence disclosure scheme - Hadjimatheou, Katerina (Policing and society, 2021)
Domestic violence disclosure schemes are being adopted by police forces in countries around the world, yet they remain controversial and empirically under-researched. This paper presents findings from the largest study of police implementation of such a scheme to date, drawing on in-depth interviews and Freedom of Information data from 12 police forces in England and Wales. We reveal that victims of domestic abuse face a ‘postcode lottery’ of disclosures, with some receiving minimal or no information about the criminal histories of their partners, and others receiving lengthy and detailed descriptions. We identify and analyse two contrasting police approaches to disclosure: ‘risk-averse’ approaches, which are driven by efforts to avoid costly legal action by disgruntled offenders, and to minimise the resource implications of the scheme; and ‘permissive’ approaches, which are more explicitly victim-centred, reflect an increasingly prevalent ‘coercive control’ discourse, and are informed and guided by close collaboration with specialist partner agencies. The discussion sheds light on the shifting culture of domestic violence policing in the UK, yields immediate recommendations for the regulation and best practice of domestic violence disclosure schemes, and has methodological implications for efforts to assess their effectiveness.